A graphical data analyzer that analysis trend of a portal traffic based on big data stored by Google Analytic - Farhan, S.M. Zamshed (BARC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2016.